The Heart and Great Vessels - Onwuka, Ekene (Cold Spring Harb Perspect Med, 2018)
Cardiovascular disease is the leading cause of mortality worldwide. We have made large strides over the past few decades in management, but definitive therapeutic options to address this health-care burden are still limited. Given the ever-increasing need, much effort has been spent creating engineered tissue to replaced diseased tissue. This article gives a general overview of this work as it pertains to the development of great vessels, myocardium, and heart valves. In each area, we focus on currently studied methods, limitations, and areas for future study.